1976
DOI: 10.1152/jn.1976.39.4.713
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of electrosensory and electromotor signals in lateral line lobe of a mormyrid fish

Abstract: A signal associated with the neural command to discharge the electric organ is recorded in cells of the lateral line lobe. Responses of cells activated by medium receptor inputs are facilitated or less frequently inhibited during this command-associated signal. Only responses to disynaptic inputs are affected, the monosynaptic response is not altered. The periods of facilitation and inhibition occur at times at which electroreceptor activity evoked by organ discharge reaches the lateral line lobe. Presumably t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(25 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…The slem receives input from MCA and thereby mediates corollary discharge-driven inhibition of nELL neurons (Fig.2), which blocks sensory responses for a brief window of time immediately after production of the fish's own EOD (Zipser and Bennett, 1976). The effects of this corollary discharge-driven inhibition can be seen downstream of the nELL, as stimuli delivered during a period of approximately 3ms starting immediately after the production of each EOD do not elicit electrosensory responses in the EL or KO region of the valvula (Amagai, 1998; Bennett and Steinbach, 1969;Russell and Bell, 1978;Szabo et al, 1979;Zipser and Bennett, 1976). Behavioral studies have confirmed that fish are less sensitive to electrosensory stimuli occurring up to 1.5ms after the fish's own EOD (Moller, 1970).…”
Section: Sensory Filtering and Temporal Sharpeningmentioning
confidence: 99%
See 2 more Smart Citations
“…The slem receives input from MCA and thereby mediates corollary discharge-driven inhibition of nELL neurons (Fig.2), which blocks sensory responses for a brief window of time immediately after production of the fish's own EOD (Zipser and Bennett, 1976). The effects of this corollary discharge-driven inhibition can be seen downstream of the nELL, as stimuli delivered during a period of approximately 3ms starting immediately after the production of each EOD do not elicit electrosensory responses in the EL or KO region of the valvula (Amagai, 1998; Bennett and Steinbach, 1969;Russell and Bell, 1978;Szabo et al, 1979;Zipser and Bennett, 1976). Behavioral studies have confirmed that fish are less sensitive to electrosensory stimuli occurring up to 1.5ms after the fish's own EOD (Moller, 1970).…”
Section: Sensory Filtering and Temporal Sharpeningmentioning
confidence: 99%
“…KO afferent fibers conduct at 40ms -1 to the ipsilateral nucleus of the electrosensory lateral line lobe (nELL) in the hindbrain (Enger et al, 1976a), where corollary discharge inhibition blocks responses to the fish's own EOD (Bell and Grant, 1989;Zipser and Bennett, 1976). That is, each time an EOD motor command is generated, nELL neurons receive inhibition that prevents them from responding to sensory input.…”
Section: A Sensory Pathway Devoted To Communication Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The Knollenorgan pathway is briefly inhibited each time a fish fires its own electric organ, resulting in a selective responsiveness to EODs produced by other individuals rather than to selfgenerated EODs (Zipser and Bennett, 1976;Mugnaini and Maler, 1987;Bell and Grant, 1989). Knollenorgan cells fire spike-like receptor potentials that are time locked to outside negative-to-positive (NrP) voltage transients (Bennett, 1971b;Szabo and Fessard, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…With each EOD, the electrosensory lobe receives both reafferent input and corollary discharge input associated with the motor command that elicits the EOD (11,12). The corollary discharge input arises from three or four different central sources (8,9,13), and the effects are both excitatory and inhibitory (7,8).…”
mentioning
confidence: 99%